Therapeutic potential of recombinant IL-22BP in psoriasis: suppression of IL-22/STAT3 signaling in mice - Xiuze Chen; Tao Zeng; Fang Fang; Qinyu Tian; Yingying Li; Wenlin Zhou; Binqian Gong; Na Tian; Jizhou Zhang; Yechen Xiao (AMB Express)
Abstract Psoriasis is a persistent immune-mediated inflammatory disorder that adversely affects the skin. Interleukin-22 (IL-22) is integral to the development and pathophysiology of psoriasis, and targeting IL-22 may serve as a promising therapeutic approach for treating the condition. IL-22 binding protein (IL-22BP) exhibits a binding affinity for IL-22 that far surpasses that of IL-22RA1 and functions as a natural antagonist of IL-22. Traditional IL-22BP production methods predominantly rely on eukaryotic animal cell expression systems, which generally require complex processes, resulting in low yield and high production costs. This study reports the expression of long-acting IL-22BP with a high yield and purity over 90% in Escherichia coli by fusion with the albumin-binding structural domain ABD. The biological functions of rhIL-22BP-ABD were assessed utilizing cell lines and a murine model. Our findings indicated that rhIL-22BP-ABD successfully suppressed IL-22-induced proliferation of HaCaT cells in vitro and alleviated imiquimod-induced psoriasis inflammation in mice. Furthermore, rhIL-22BP-ABD can effectively inhibit the signaling of its downstream signaling pathway STAT3 and the associated inflammatory factors by binding to IL-22, which is beneficial to the recovery of psoriasis. These findings provide a basis for forthcoming extensive studies on the rhIL-22BP-ABD protein for industrial manufacturing and pharmaceutical development.